Peran Asesmen Psikologi Dalam Menemukan Arah Konseling - Maulidia Aulia Putri (Jurnal Pendidikan Sosial Dan Konseling, 2025)
A key component of guidance and counseling practice is psychological assessment, which is essential for a thorough and impartial understanding of the counselee's condition. Assessments allow counselors to examine the underlying cognitive, affective, and behavioral components of the counselee, in addition to the obvious ones. This article aims to examine the strategic role of psychological assessment in helping counselors understand the characteristics, needs, and potential of the counselee during counseling sessions. Not only as a data collection tool, assessment is also a tool to determine effective interventions. This research uses a qualitative method with a library approach by reviewing some literature that is considered relevant. The concept of psychological assessment, ethics and basic principles of implementation, types of test and non-test assessments, and their role in the counseling process - from diagnostic, predictive, to evaluative - are some of the facts studied. The findings show that assessment is more than just a tool to measure; it is an essential component of the counseling process that supports the accuracy of services, the depth of understanding of the counselee, and the direction of more sympathetic and successful interventions. Therefore, professional counselors should have a strong understanding of assessment as well as counselor personal development.